Implementasi Sistem Arsip Berbasis Website Pada Badan Kepegawaian Daerah Kota Samarinda - Nanda Betris Dea Maretta; Abdul Rahim; Khanisa Octavia; Alvinalia Alvinalia; Aprilian Habar (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
Archiving is nothing new for agencies. The movement of documents and other documents in and out of government agencies certainly requires filing. The storage carried out at the Samarinda City Regional Civil Service Agency Office has not been fully effective for the existing archives, because some of the archives carried out are still done manually. As a result, archives can easily be lost before archiving or data management is done, often requiring manual intervention. Storage usage causes errors in storing data and retrieving data. This website-based archive system is indispensable, this is because it can be used to make changes to data, such as reducing the amount of paper used and changing the way data is stored (going paperless). This archive website system was created using the Vscode application. Where the Programming Language used is PHP and SQL, with Xampp used for web server operations and SQL for database management, by sending letters paperlessly will minimize errors that have occurred so far. While the software development method or system design uses the Waterfall method. Waterfall methodology is a type of application development model that is integrated into the classic life cycle. The purpose of making this website is to create a website system that processes email archive data in an easy-to-use way.